2014
DOI: 10.1002/pola.27307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of degradable molecular brushes via a combination of ring‐opening polymerization and click chemistry

Abstract: Acid‐degradable molecular brushes with polycarbonate backbone and densely grafted side chains (∼1.9 SCs per backbone repeating unit) were synthesized for the first time using the grafting‐onto method. Extremely efficient copper‐catalyzed azide‐alkyne cycloaddition click reactions between the polycarbonate backbone containing two pendant azido groups per backbone unit and alkynyl‐terminated poly (methyl acrylate) (ay‐PMA72, average degree of polymerization DP = 72) SCs were demonstrated to finish in 10 min with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…This provides a facile platform for the synthesis of functional aliphatic polycarbonates. According this useful approach, palmitate, poly(methyl acrylate), polystyrene, and poly( t ‐butyl acrylate)‐ block ‐polystyrene were successfully grafted to the polycarbonate backbone to generate amphiphilic block‐graft copolymers or degradable molecular brushes. Using monomethoxy poly(ethylene glycol) as an initiator, amphiphilic block copolymer PEG‐ b ‐P(DTC‐ADTC) bearing the pendant azide groups could be synthesized for preparing core‐shell redox‐responsive polymeric micelles in which the cores are crosslinked via click chemistry with the disulfide‐containing dialkyne as the crosslinker to enhance the stability of the micelles and improve the drug‐loading property .…”
Section: Click Chemistry In the Synthesis Of Functional Aliphatic Polmentioning
confidence: 99%
“…This provides a facile platform for the synthesis of functional aliphatic polycarbonates. According this useful approach, palmitate, poly(methyl acrylate), polystyrene, and poly( t ‐butyl acrylate)‐ block ‐polystyrene were successfully grafted to the polycarbonate backbone to generate amphiphilic block‐graft copolymers or degradable molecular brushes. Using monomethoxy poly(ethylene glycol) as an initiator, amphiphilic block copolymer PEG‐ b ‐P(DTC‐ADTC) bearing the pendant azide groups could be synthesized for preparing core‐shell redox‐responsive polymeric micelles in which the cores are crosslinked via click chemistry with the disulfide‐containing dialkyne as the crosslinker to enhance the stability of the micelles and improve the drug‐loading property .…”
Section: Click Chemistry In the Synthesis Of Functional Aliphatic Polmentioning
confidence: 99%
“…Thus, the research of molecular brushes is inspired by the biological brushes and they have potential applications in biomimetic field. Thanks to the development of living/controlled radical polymerization, including atom transfer radical polymerization (ATRP) [9,10], reversible addition-fragmentation chain transfer polymerization (RAFT) [11], and nitroxide mediated polymerization (NMP) [12], and robust synthetic routes, like ''click'' chemistries [13][14][15][16][17], the molecular brushes with controlled molecular weight, narrow molecular weight distribution and well-defined structures can be synthesized via ''grafting from'', ''grafting through'' or ''grafting to'' method [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[15a,17] In studies of cleavable/degradable bottlebrush polymers, Müller's group reported core–shell cylindrical brushes with acid‐degradable cores, which were used to prepare hollow nanotubes . Shi et al prepared an acid‐degradable bottlebrush polymer with a polycarbonate backbone and densely grafted side chains . Jiang's group reported a reducible and degradable brushed poly(2‐(dimethylamino) ethyl methacrylate and evaluated its gene delivery .…”
Section: Introductionmentioning
confidence: 99%